Procesos Disciplinarios en contra de los Jueces por dolo, error inexcusable o negligencia manifiesta, Análisis Probatorio - Cruz Toscano, José Eduardo (2019)
The administrative responsibility is that in which the public judicial servant incurs by actions or omissions committed in the exercise of his position that produce an injury or damage to the interests of the State, public or private servants, which originates the imposition of sanctions when previously the due process of disciplinary proceedings has been followed, especially when it is directed against the administrators of justice. By virtue of the foregoing, it is stated that if a Judge incurs administrative liability, he may be dismissed from his position, but also civil or criminal actions may be initiated against him according to the nature of the offense, especially when they committed serious or very serious offenses. established in the Organic Code of the Judicial Function, whose consequence is the loss of the position of Judge. With this background, it is evident that in this work there is evidence of the need for the legal system to establish that only Judges can request or dispose the administrative bodies of the Judicial Branch the initiation of disciplinary proceedings for inexcusable error or gross negligence in against a Judge, because the administrators of justice are in the capacity to determine if a Judge acted with evident negligence or error at the moment of applying the law; but not the administrative public officials, the same ones who should initiate disciplinary proceedings after a predetermination of responsibilities by one Judge against another, but not directly or ex officio. The execution of the investigation will benefit the independence of the Judicial Function, since the inexcusable error has been a legal instrument that has sometimes led to the dismissal of a Judge, without major legal arguments or without fully verifying that the same incurred in an infraction, that is to say when it was not demonstrated through the various means of proof that the Judge incurred an administrative infraction.